Efficacy and safety of topical versus intravenous tranexamic acid in spinal surgery: a systematic review and meta-analysis - Chengxin Xie; Liwei Zhang; Guoping Cai; Yongwei Su; Peng Wang; Hua Luo (BMC Surgery)
Abstract Background The relative efficacies of topical and intravenous tranexamic acid (TXA) in spinal surgery remain controversial. This meta-analysis aimed to compare the efficacy and safety of topical versus intravenous TXA in spinal surgery, with a particular focus on the impacts on intraoperative blood loss (IBL) and associated outcomes. Methods We searched the PubMed, EMBASE, Medline, and Cochrane Library databases to identify all literature related to topical and intravenous TXA in spinal surgery. Six trials met the inclusion criteria. The IBL, postoperative drainage volume, total blood loss, postoperative hematological variables, postoperative blood transfusions, and complications were analyzed. Results The meta-analysis of randomized controlled trials indicated that IBL and total blood loss were markedly higher in the group receiving topical TXA compared to the intravenous TXA group. Conversely, data from retrospective studies did not show significant differences between the two groups. Hemoglobin levels on postoperative days 1 and 3 were significantly lower in the topical TXA group than in the intravenous TXA group. No significant differences were observed between the topical and intravenous TXA groups regarding other postoperative hematological parameters, drainage volume, transfusion rates, and complications. Conclusions The current evidence suggests that topical TXA does not significantly reduce postoperative blood loss in spinal surgery compared with intravenous TXA, but has good safety and does not increase the associated risks. There is a need for high-quality studies that explore the effects of topical TXA in spinal surgery.